a The Relation Between The Availability of Farmer Households Staple Food and Farmers’ Mental Health in Lebak Pering Village South Pemulutan District Ogan Ilir Regency: Hubungan Ketersediaan Pangan Pokok Rumah Tangga Petani Terhadap Kesehatan Mental Petani Di Desa Lebak Pering Kecamatan Pemulutan Selatan Kabupaten Ogan Ilir - Nurilla Elysa Putri; Lismawati, Yesi (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
Farmer profession with a job perspective that has a low income. Economic problems increase the probability that farmers will experience health problems, whether physical, psychological or mental, thus affecting the farmer's emotional condition. Researchers are interested in examining the impact of the availability of staple food for farming households in Lebak Pering Village as a priority food insecure village on the mental health conditions of farmers as the main profession in the village. The purpose of this research are: (1) To describe the condition of the availability of farmer hosehold staple food in Lebak Pering Village, Pemulutan District, (2) Knowing condition of farmers’ mental health problems in Lebak Pering Village, South Pemulutan District, (3) To know the relationship between the availability of farmer household staple food to farmers’ mental health at Lebak Pering Village, South Pemulutan District. This research conducted in Lebak Pering Village, South Pemulutan District, Ogan Ilir Regency. This location was selected purposively which consider as a priority area of food insecurity. The data which collected was carried out from desember 2021 to February 2022. The research method used is survey method and the sampling method used is simple random sampling which is 30 samples considered homogeneous as a farmers using rainfed system with land area less than 3 hectares and including as the third priority area of food insecurity. The results of this research are: (1) Staple food availability of farmer household as a low availability category about 60% with average 906 kilograms per capita per year, (2) The mental health problems condition of farmers includes as a high category about 70,60, (3) There is correlation between food availability and selfvalue of farmer. However, there is no direct correlation between food availability and anxiety, pressure and interpersonal relationship of farmers at Lebak Pering Village.